Letter to George Grimes; from Louis R. Nash - Louis R. Nash:::::: (1964)
This letter was to George Grimes from Louis R. Nash sent on January 20, 1964. Louis R. Nash sent this letter to thank George Grimes for his great efforts as the most active chairman. Grimes outstanding performance and administration to bring together various staff and meet was being recognized in this letter, feedback on January 18th meeting.